Imidazoline receptors in the heart: a novel target and a novel mechanism of action that involves atrial natriuretic peptides - Mukaddam-Daher,S. (2004)
Chronic stimulation of sympathetic nervous activity contributes to the development and maintenance of hypertension, leading to left ventricular hypertrophy (LVH), arrhythmias and cardiac death. Moxonidine, an imidazoline antihypertensive compound that preferentially activates imidazoline receptors in brainstem rostroventrolateral medulla, suppresses sympathetic activation and reverses LVH. We have identified imidazoline receptors in the heart atria and ventricles, and shown that atrial I1-receptors are up-regulated in spontaneously hypertensive rats (SHR), and ventricular I1-receptors are up-regulated in hamster and human heart failure. Furthermore, cardiac I1-receptor binding decreased after chronic in vivo exposure to moxonidine. These studies implied that cardiac I1-receptors are involved in cardiovascular regulation. The presence of I1-receptors in the heart, the primary site of production of natriuretic peptides, atrial natriuretic peptide (ANP) and brain natriuretic peptide (BNP), cardiac hormones implicated in blood pressure control and cardioprotection, led us to propose that ANP may be involved in the actions of moxonidine. In fact, acute iv administration of moxonidine (50 to 150 µg/rat) dose-dependently decreased blood pressure, stimulated diuresis and natriuresis and increased plasma ANP and its second messenger, cGMP. Chronic SHR treatment with moxonidine (0, 60 and 120 µg kg-1 h-1, sc for 4 weeks) dose-dependently decreased blood pressure, resulted in reversal of LVH and decreased ventricular interleukin 1ß concentration after 4 weeks of treatment. These effects were associated with a further increase in already elevated ANP and BNP synthesis and release (after 1 week), and normalization by 4 weeks. In conclusion, cardiac imidazoline receptors and natriuretic peptides may be involved in the acute and chronic effects of moxonidine.